2010
DOI: 10.1021/ja908419j
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Processing of Platinated RNAs

Abstract: The broadly prescribed anti-tumor drug cisplatin coordinates to DNA, altering the activity of cellular proteins whose functions rely upon sensing DNA structure. Cisplatin is also known to coordinate to RNA, but the effects of RNA-Pt adducts on the large number of proteins that process the transcriptome are currently unknown. In an effort to address how platination of an RNA alters the function of RNA processing enzymes, we have determined the influence of [Pt(NH3)2]2+-RNA adducts on the activities of 3’ → 5’ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 65 publications
5
38
0
Order By: Relevance
“…addition, cisplatin causes atypical cross-links in structurally complex RNAs, thereby preventing reverse transcription, indicating that the RNA binding may interfere with communicating sequence information (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…addition, cisplatin causes atypical cross-links in structurally complex RNAs, thereby preventing reverse transcription, indicating that the RNA binding may interfere with communicating sequence information (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…A preference for interaction with the guanine base is observed for both compounds, in agreement with previous studies by us and others. 27,33À36 Depending on the more extended sequence context, different binding preferences are observed for the two studied metal complexes, however.…”
mentioning
confidence: 99%
“…A recent study also demonstrated that cisplatin, oxaliplatin and carboplatin have different effects on mRNA translation in vitro [74]. Moreover, RNA-cisplatin adducts have been shown to inhibit the function of some RNA processing enzymes in vitro [75]. Interestingly, inductively coupled plasma mass spectrometry (ICP-MS) was recently used to show that platinum accumulates in total 4-to 20-fold more in total cellular RNA than in genomic DNA upon cisplatin treatment of Saccharomycie cerevisiae (S. cerevisiae) [76].…”
Section: Platinum Binding To Rnamentioning
confidence: 99%
“…This rapid crosslink formation in an internal loop of a structurally complex RNA may in principle affect RNA dynamics and function [80]. However, the effect of RNA-platinum binding on cell functions is still largely unknown [39,75].…”
Section: Platinum Binding To Structured Rnas: the Case Of Spliceosomamentioning
confidence: 99%